Duality of the alternating integral for quasilinear differential games - Iskanadjiev, Ikrom (Nonlinear Analysis: Modelling and Control, 2012)
The concept of alternated integrals proved to be useful in differential games and in control theory under the conditions of uncertainty. In this article the connection between upper and lower alternating integrals for quasi-linear differential games is established and its applications to the problem of pursuit is studied.
Keywords: differential games; alternating integral; multi-valued mapping; pursuer; evader; strategy